Secondary school students’ lack of mathematics understanding - Masomeh Jamshid Nejad (Northwest Journal of Teacher Education, 2012)
A study was conducted to investigate the influence of pupils’ beliefs on their performance in problem solving. Twenty-seven students from Grade 8 participated in this study. The findings showed that there is a positive correlation between participants’ belief, some subscales of belief and participants’ performance in problem solving. Further research was then suggested. A study was conducted to investigate the influence of pupils’ beliefs on their performance in problem solving. Twenty-seven students from Grade 8 participated in this study. The findings showed that there is a positive correlation between participants’ belief, some subscales of belief and participants’ performance in problem solving. Further research was then suggested.